PERANCANGAN PENINGKATAN DAYA SAING UKM BANDENG DI KABUPATEN SIDOARJO DENGAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) - Wulandari, Rina Sri (Journal of Research and Technology, 2018)
Sidoarjo has become one of the districts with the largest number of SMEs and milkfish processing SMEs being one of the superior in Sidoarjo Regency. However, the increasing number of milkfish processing industries even from outside Sidoarjo Regency has caused this industry to be able to compete with various similar businesses from various regions. Therefore, a strategy is needed to improve the competitiveness of processed milkfish. From these problems, the design of increasing the competitiveness of SMEs was carried out with the method of Quality Function Deployment (QFD). The QFD method is used because this method can be used to plan and develop products in a structured manner and allow the development team to clearly define customer needs and expectations, and evaluate the ability of a product or service systematically to meet those needs and expectations. Customer needs and expectations based on the House of Quality matrix consist of 4 indicators including products, prices, packaging, and marketing. While the criteria used were 14 criteria. Development priorities based on House of Quality are marketing, packaging design, quality of additional materials, quality of raw materials, content of additional materials, production equipment, and use of packaging materials.